Performance analysis of MIMO-CDMA system - Ngajikin, Nor Hafizah; Nik Abd. Malik, Nik Noordini; Mohd. Esa, Mona Riza; Idrus Sutan Nameh, Sevia Mahdaliza; Ramli, Noorliza (2006)
Nowadays, the demand on communication system is towards high capacity and faster data transmission with minimum error or losses. In wireless communication, multiple input multiple output (MIMO) is one of the techniques that can increase spectral efficiency and link reliability. Therefore, the performance of MIMO-CDMA with comparison to conventional code division multiple access (CDMA) system has been analyzed. The simulations models are simulated with different number of antenna which are two transmit-two receive (2Tx2Rx) and four transmit-four receive (4Tx4Rx). System specification is based on voice application. The simulation results shows that the proposed MIMO-CDMA (2Tx2Rx) is improved by 43% of BER and MIMO-CDMA (4Tx4Rx) improved by 63% of BER performance compared to conventional CDMA. Capacity performance of MIMO-CDMA (2Tx2Rx) improved by 50% and MIMO-CDMA (4Tx4Rx) improved by 75% compared to conventional CDMA.